Effect of viscosity on photodegradation rates in complex secondary organic aerosol materials. Issue 13 (21st December 2015) - Hinks, Mallory L.; Brady, Monica V.; Lignell, Hanna; Song, Mijung; Grayson, James W.; Bertram, Allan K.; Lin, Peng; Laskin, Alexander; Laskin, Julia; Nizkorodov, Sergey A.
Abstract : This work explores the effect of environmental conditions on the photodegradation rates of atmospherically relevant, photolabile, organic molecules embedded in a film of viscous secondary organic material (SOM). Abstract : This work explores the effect of environmental conditions on the photodegradation rates of atmospherically relevant, photolabile, organic molecules embedded in a film of secondary organic material (SOM). Three types of SOM were studied: α-pinene/O3 SOM (PSOM), limonene/O3 SOM (LSOM), and aged limonene/O3 obtained by exposure of LSOM to ammonia (brown LSOM). PSOM and LSOM were impregnated with 2, 4-dinitrophenol (2, 4-DNP), an atmospherically relevant molecule that photodegrades faster than either PSOM or LSOM alone, to serve as a probe of SOM matrix effects on photochemistry. Brown LSOM contains an unidentified chromophore that absorbs strongly at 510 nm and photobleaches upon irradiation. This chromophore served as a probe molecule for the brown LSOM experiments. In all experiments, either the temperature or relative humidity (RH) surrounding the SOM films was varied. The extent of photochemical reaction in the samples was monitored using UV-vis absorption spectroscopy. For all three model systems examined, the observed photodegradation rates were slower at lower temperatures and lower RH, conditions that make SOM more viscous. Additionally, the activation energies for photodegradation of each system were positively correlated with the viscosity of the SOM matrix as measured in poke-flow experiments. These activation energies were calculated to be 50, 24, and 17 kJ mol −1 for 2, 4-DNP in PSOM, 2, 4-DNP in LSOM, and the chromophore in brown LSOM, respectively, and PSOM was found to be the most viscous of the three. These results suggest that the increased viscosity is hindering the motion of the molecules in SOM and is slowing down their respective photochemical reactions.